Effect of retaining wall leakage on the deformation behavior of foundation pit in water-rich sandy strata - Mingming QIU; Xiaomin LI; Guolin YANG; Junyi DUAN (Shuiwen dizhi gongcheng dizhi)
Aiming at the disaster problem caused by leakage of water and sand in deep excavation, it is of great significance to reveal the evolution of foundation pit leakage disaster and its control method for underground engineering construction safety. Based on the leakage disaster of row-pile retaining deep foundation pit induced by deep excavation in water-rich sandy strata, the development characteristics and causes of leakage of water and sand during construction were analyzed, and the deformation behavior of foundation pit and its control measures under partial leakage were investigated by field monitoring and numerical simulation method. The results show that the development of leakage disaster of foundation pit is a complicated multi-field coupling process, and its occurrence is hidden and sudden. The horizontal displacement curve of retaining wall successively transformed from “oblique” shape, “bottom of pot” shape, shallow “inverted V” shape to deep “inverted V” shape with excavation depth. The maximum horizontal displacement of the retaining wall after leakage is 1.29 to 1.44 times larger than before leakage. The ground settlement curve of behind the retaining wall successively transformed from “flat ladle bottom” shape, “shallow ladle bottom” shape to “deep ladle bottom” shape with excavation depth; the sensitive zone of settlement trough is 1.00he to 1.20he (he is excavation depth). The ground settlement trough deepens and widens due to partial leakage, and the maximum ground settlement after leakage is 1.16 to 1.65 times that before leakage. The characteristics of the “jump” fluctuation of groundwater level can be used as the precursor signal to judge the leakage disaster of foundation pit. The change of supporting axial force is dynamically adjusted with the process of excavation and support to coordinate the development of deformation, and the supporting axial force fluctuates slightly during retaining wall leakage. The combined treatment measures of grouting and high pressure rotating spouting pile can effectively deal with the problem of leakage disaster control of foundation pit in water-rich sandy strata. This study can provide basic information for the theoretical analysis and control of leakage disaster of foundation pit.